(untitled) (Research, Society and Development, 2020)
Tooth avulsion is the displacement of the tooth out of its socket, being more prevalent in sports and automobile accidents. Among the treatment options stands out the dental replantation, which represents one of the most appropriate conducts in dentistry, if used properly. Considering that nursing and physical education professionals have greater direct or indirect contact with this type of injury, this study aimed to identify the knowledge of students of the eighth semester of Nursing and Physical Education courses at a University of Southern Brazil, about avulsion. and dental replantation technique. Participated in the study 105 students of Nursing and Physical Education. Knowledge was assessed from a questionnaire containing objective questions about the proposed theme. 81.5% of the students interviewed reported not having studied undergraduate subjects related to dental trauma and 90.5% had not attended cases of dental avulsion. Participants stated that they would wash their teeth with tap water (36.1%) and keep them in a clean napkin until specialized care (46.6%). It is concluded the need for discussion of the theme in the curriculum matrix of the researched courses, given the lack of knowledge of immediate procedures in cases of avulsion.